Pulmonary insufficiency of extreme prematurity (PIEP) and surfactant deficiency disease (SDD) - It is time to classify respiratory distress syndrome (RDS) in preterm neonates - Deepti Thandaveshwara; Sushma Krishnegowda; Srinivasa Murthy Doreswamy (Hygeia Press di Corridori Marinella, 2024)
Respiratory distress in premature neonates is the consequence of various pathophysiologic conditions.  The respiratory distress syndrome (RDS) is commonly considered as the consequence of pulmonary surfactant deficiency; these babies generally respond well to exogenous surfactant.  In extremely premature babies, overall physiological immaturity of the lungs secondary to prematurity itself plays a significant role in respiratory illness; the therapeutic response to continuous airway distending pressure or surfactant is not very impressive in these babies, who continue to need an extended period of respiratory support and eventually end up in developing bronchopulmonary dysplasia.  This article aims to highlight the importance of the difference between primary surfactant deficiency disease (SDD) and pulmonary insufficiency of extreme prematurity (PIEP).  This classification may help in drawing up more appropriate treatment plans and reduce the gestation-related skewed outcomes in future research.